(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article deals with the essence of KPI (key performance indicators), which are relatively new and relevant in the higher educational system, and their role in the reputation and development of institutions, as well as some analysis of its creation and implementation.